Innovation Patterns in Islamic Education Learning Management: A Qualitative Case Study at SDIT Tahfizh Qur'an Al-Jabar Karawang in the Digital Disruption Era - Vina Febiani Musyadad; Kartimi Kartimi; Iman Subasman; Abdul Karim; Jalaludin Jalaludin; Muhammad Sultan Alikhan (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2026)
The rapid advancement of digital disruption has forced Islamic educational institutions to transform their learning management systems while maintaining spiritual values. This qualitative case study aims to analyze the patterns of innovation in Islamic Education learning management at SDIT Tahfizh Qur'an Al-Jabar Karawang. Data were collected through in-depth interviews with the principal, teachers, and education staff, participant observation over six months, and document analysis, then analyzed using Miles and Huberman’s interactive model. The findings demonstrate systematic innovation across three domains: planning that integrates digital tools with students’ Qur’anic memorization levels and characteristics; implementation that combines conventional methods with interactive digital media, resulting in an 85% increase in student motivation; and evaluation through application-based assessments that achieve 94% data accuracy while monitoring both spiritual and academic competencies. This study reveals that technology integration does not erode Islamic values but instead creates a balanced “value-based technological moderation” model. The scientific novelty of this research lies in presenting an empirically grounded, replicable framework of Islamic learning management that harmoniously combines digital innovation with tahfizh-based spiritual formation in an elementary school setting. Theoretically, it bridges innovation theory, values-based management, and religious moderation; practically, it provides a concrete reference for other Islamic schools navigating digital transformation without losing their religious identity.